Digitalizing the Learning Experience in Life-Sciences during the Covid-19 Pandemic in Japan - Alexandra DUTESCU DIMBOVITA; Keita SUGIYAMA; Hideki ISHIDA; Hiroaki KANEKO; Cristian Iulian VLAD (Communications of International Proceedings, 2021)
This paper focuses on the HR transformation within a leading Japanese pharmaceutical company, and provides an overview on the impact held by the implementation of new technology solutions. This research will highlight the organizational culture changes undergone through digital learning transformation, such as talent reskilling/upskilling and employee empowerment supported by the integration of a new Learning Management System (LMS). The authors engaged with Talent Managers and Operators from the Japanese Life-Sciences organization working in HR, Talent and Organizational Development, Executive Management, and consulting collaborators.
Keywords: Talent; Life-Sciences; Organization; Technology; Digitalization; Management; Covid-19; Learning; Japan